Wednesday

April 23, 2014

April 23, 2014

Posted by **Wenny12** on Wednesday, April 20, 2011 at 12:18am.

Use Gauss-Jordan to solve

3x – 2y + z = 6

3x + y – z = -4

-x + 2y – 2z = -8

- Alg 2 - Math -
**MathMate**, Sunday, April 24, 2011 at 6:20amStart by transcribing the equations to a 3x4 matrix

3 -2 1 6

3 1 -1 -4

-1 2 -2 -8

The first step is to reduce each column to zero (except the diagonal element and above) by linear combination of rows. I'll do the first one:

3 -2 1 6

0 3 -2 -10 (row 2 - row 1)

0 4 -5 -18 (3*row 3 + row 1)

Continue:

3 -2 1 6

0 3 -2 -10

0 0 7 14 (4*row 2 - 3*row 3)

The last row can be simplified:

3 -2 1 6

0 3 -2 -10

0 0 1 2

So z=2, substitute z=2 in row 2 to eliminate elements above the diagonal

3 -2 0 4 (row 1 - row 3)

0 3 0 -6 (row 2 + 2*row 3)

0 0 1 2

Simplify row 2:

3 -2 0 4

0 1 0 -2 (row 2/3)

0 0 1 2

Now eliminate column 2 from row 1

3 0 0 0 (row 1 + 2*row 2)

0 1 0 -2

0 0 1 2

So

x=0

y=-2

z=2

**Related Questions**

math - solve by the gauss-jordan method x+y+z=6 3x+2y-z=4 3x+2y+2z=11

Algebra - Use Gauss-Jordan to solve 3x + 2y = -4 4x – 2y = -10

Algebra - Use Gauss-Jordan to solve 3x + 2y = -4 4x – 2y = -10

algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...

Algebra - I need help on this one too, please. Solve for X. 3x-2y=6 I got x=6+2y...

algebra - needing help with is problem solve for x: 3x-2y=-6 here is my solution...

algebra - 2x +y+3z=-1,(a+3)x+2y+8z=2,3x+y(a+1)z=1 solve for a, by gauss-jordan ...

maths - use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 ...

math correction - solve for x: 3x - 2y = 6 i need help in solving this: the ...

Algebra - What is the standard form of the equation of the line passing through ...